Peer group influence on academic achievement among male students at higher institution in Sarawak - Buang, Fakhzan; Darusalam, Ghazali (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This study was designed to investigate the significance relation between peer group influence and the academic achievement among male students at one of higher institution in Sarawak, Malaysia. A total of 254 male students from different fields of study, and academic year were randomly selected, and majority of them were diploma students. Their academic achievement indication was measured based on the students’ latest final examination results. A self-developed questionnaire was used, to determine the relationship between factors in selecting peers, types of peer influences, relationship with peer group, and effects of peer group influence towards academic achievement. The statistical analysed data tested three hypotheses in this study, and showed that, there was not any significant relationship between factors in selecting peers and academic achievement of male students, and types of peer group influence was significant related towards academic achievement. The finding of regression analysis indicated only effect of peer group influence affected male’s student academic achievement. These findings led to agreement that peer group influence positively related with academic achievement of male students at higher learning. Therefore, the present research recommended other related variables in peer group influence that affects students’ academic achievement should be addressed, and in-depth comparative study need to be conducted in future research.